PENGGUNAAN TEKNOLOGI E-BANKING DALAM SISTEM INFORMASI MANAJEMEN PERBANKAN SYARIAH - Aulia Rahma; Devi Andriyani, Farida Syah Damanik, Muhammad Hafizhan Fakhri, Nurbaiti (CV. ADIBA AISHA AMIRA, 2024)
E-banking technology is one of the important factors in improving the efficiency and effectiveness of Islamic banking operations. This study applies a descriptive qualitative research method to examine in depth the implementation of e-banking in Islamic bank information management. The purpose of this study is to explore the use of e-banking technology in the Islamic banking management system and to determine the benefits and challenges in its implementation for Islamic banking operations. The benefits include low transaction costs, ease of unlimited transactions, high data security and accessibility that makes it easy for customers to access banking services anytime and anywhere. The challenges faced by Islamic banks in the digital transformation process include data security and privacy, infrastructure and resource readiness, adaptation of organizational culture, and compliance with Islamic regulations. To overcome these challenges, the author argues that Islamic banks need to take strategic steps. Further research is needed to explore the long-term impact of e-banking on customer satisfaction and the financial performance of Islamic banks